Bifurcation analysis of a magnetically supported rigid rotor in auxiliary bearings. (January 2019) - Liu, Xijuan; Liu, Yun; Wang, Shuguo; Yan, Huijie; Liao, Pengtai
Abstract: The stability and bifurcation behavior of a kind of active magnetic bearing rotor are investigated in this paper. The analysis is carried out both analytically and numerically. It is found that a Hopf bifurcation occurs in the system by using center manifold and normal form. Numerical simulation is conducted to validate the theoretical predictions. More precisely, the dynamic characteristics of this system in two-dimensional parameter space are analyzed, the phase diagrams assist us to identify multi-attractor coexisting that makes the dynamical behaviors of the system become more enrich and complex. These results we represent can be useful in designing and selection of suitable operating parameters. As a result, the system can avoid the undesirable behavior.